2022
DOI: 10.3390/su14084800
|View full text |Cite
|
Sign up to set email alerts
|

The Influence Mechanism of Strategic Partnership on Enterprise Performance: Exploring the Chain Mediating Role of Information Sharing and Supply Chain Flexibility

Abstract: In the context of the digital economy, establishing close strategic partnerships to cope with market uncertainties is an important strategic choice for firms seeking to achieve sustainable development in developing countries, particularly in Eastern culture. However, research on how strategic partnerships affect enterprise performance remains controversial. To address this issue, based on the supply chain management practices of Chinese enterprises in the era of the digital economy, and according to resource d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 109 publications
1
3
0
Order By: Relevance
“…Employing network theory to explain the relationships between Industry 4.0, SCC, SCF and CI, the study found, in line with the network theory literature, that interaction and strong connections, role of networks and the flow of information and knowledge among network partners benefit supply chain performance (Dekkers et al, 2020;Tan et al, 2023). SCF is influenced by collaboration, information sharing and exchange connections among partners; therefore, it is important for improving supply chain performance (Yang et al, 2022;Pellegrino et al, 2023). Additionally, cost reductions in supply chains enable companies to adapt to new global markets and improve performance (Sharma et al, 2022).…”
Section: Theoretical Contributions and Implicationssupporting
confidence: 54%
See 1 more Smart Citation
“…Employing network theory to explain the relationships between Industry 4.0, SCC, SCF and CI, the study found, in line with the network theory literature, that interaction and strong connections, role of networks and the flow of information and knowledge among network partners benefit supply chain performance (Dekkers et al, 2020;Tan et al, 2023). SCF is influenced by collaboration, information sharing and exchange connections among partners; therefore, it is important for improving supply chain performance (Yang et al, 2022;Pellegrino et al, 2023). Additionally, cost reductions in supply chains enable companies to adapt to new global markets and improve performance (Sharma et al, 2022).…”
Section: Theoretical Contributions and Implicationssupporting
confidence: 54%
“…, 2023). SCF is influenced by collaboration, information sharing and exchange connections among partners; therefore, it is important for improving supply chain performance (Yang et al. , 2022; Pellegrino et al.…”
Section: Discussionmentioning
confidence: 99%
“…With the deep integration of the BSC with the Internet and the Internet of Things, this relationship is constantly strengthened. Resource sharing among integrated BSC (IBSC) enterprises has gradually become the new normal [8]. The development of DGI among these enterprises has gradually become a suitable DGI mode.…”
Section: Introductionmentioning
confidence: 99%
“…Information exchange, in particular, tends to affect technology (BDA adoption)-effect (firm performance) relationships [23,29,30]. As reported by Yang, Zheng, Xie, and Tian [31], the influence of technology on information exchange remains an existential question. Therefore, the mechanism by which knowledge sharing influences technology-impact interactions merits additional investigation.…”
Section: Introductionmentioning
confidence: 95%